(3cJGH GdefGXQs - (3GbdjOSs
(3ChdgG (B:s
(3gPG GdcJGH JMOK HGSJeOGO ef GdCLQGe GdfjQI ai GdLSe GdTaGa GdeJhSW HjfgG hHjf GdeHUQGJ cGdghGA heG TGcdg s
(3BNQgG (B:s
(3aEPf GdCVdGY eJSGhjI ai GdQDjI hcPdc GdbQWGf hPdc eG CQOfGg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3GdfSNI HgG MhGTs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1463s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs